Identification of a chromatin regulator signature and potential prognostic ability for adrenocortical carcinoma - Li, Junwu; Jia, Yuanzhen; Tang, Lin; Zhang, Ronggui; Zhang, Yuanfeng (Frontiers in Genetics, 2022)
Objective: Adrenal cortical carcinoma (ACC) is a rare malignant tumor. Chromatin regulators (CRs) can drive epigenetic changes, which have been considered as one of the most important hallmarks of tumors. This study aimed to explore CRs for ACC, so as to clarify the molecular basis of ACC’s pathogenic mechanism and offer new methods to diagnose and treat ACC clinically. Methods: This work obtained transcriptome sequencing datasets of ACC patients and sequencing data of normal adrenal tissues in TCGA and GTEx databases, respectively. Meanwhile, prognostic genes were selected through LASSO and Cox regression. Then, this work constructed the risk model for predicting ACC prognosis. In addition, we also carried out KM analysis for assessing the differential survival between low- and high-risk groups. TIMER 2.0 was used to assess differences in immune infiltration between two groups. Further, this work utilized R package "pRRophetic" for analyzing and estimating sensitivity of patients to different chemotherapeutic agents. Results: A 5-CRs model was established to predict ACC survival, and CRs feature was confirmed as a factor to independently predict ACC patient prognosis. Also, a nomogram composed of risk score and T stage performed well in predicting patient prognosis. CRs were mostly associated with cell cycle, base excision repair and other signaling pathways for high-risk group. As for low-risk group, CRs were mainly enriched in allograft rejection, cytochrome P450 drug metabolism, and other signaling pathways. As proved by TIMER analysis, low-risk group had higher proportions of common myeloid progenitor cells (MPCs), natural killer (NK) cells and mast cells, whereas lower proportions of CD4+ T cells, macrophages, eosinophils, and monocytes. Besides, high-risk cases showed higher sensitivity to etoposide and doxorubicin. Additionally, low-risk patients had markedly decreased expression of RRM1 compared with high-risk cases, suggesting the better effect of mitotane treatment. Conclusion: This study identified the differentially expressed CRs, which might be related to ACC genesis and progression. Additionally, the pathways enriched by these CRs were screened, and these CRs were verified with excellent significance for estimating ACC survival. These drug sensitivity analysis results will provide reliable ideas and evidence for diagnosing and treating ACC in clinic.